Undang-Undang Informasi dan Transaksi Elektronik dalam Konteks Maqasid Syari'ah - Hadi, Abdul; Nugroho, Bekti Taufiq Ari; Muntakhib, Ahmad; Choeroni, Choeroni (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
The fundamental values Ã¢â‚¬â€¹Ã¢â‚¬â€¹contained in Islamic law are reflected in the formulation of Islamic law itself, namely happiness, enjoyment, benefit, justice, and so on. The online system has the potential to conflict with the values Ã¢â‚¬â€¹Ã¢â‚¬â€¹of Islamic law, which is detrimental to many people because of the difficulty of tracking various electronic transactions and it can have a very broad impact when it comes to crimes in the digital world. Based on this reality, several research problems arise related to the ITE Law from the perspective of maqÃ„ÂÃ¡Â¹Â£id shari'ah. This article is a library research study using a qualitative paradigm. The results of the discussion show that the emergence of social groups in the name of religion that misuse social media has occurred, one of which is spreading hoax news, updating news, photos, and videos, etc. that deviate from existing norms. The ITE Law is a new thing in the realm of legislation in Indonesia. For that, it is necessary to study further, one of which is in terms of maqÃ„ÂÃ¡Â¹Â£id syarÃ„Â«'ah the extent to which the objectives of the law are viewed from Islamic law or qawÃ„Â'id uluhiyyah. The relevance of maqÃ„ÂÃ¡Â¹Â£id syarÃ„Â«'ah with the ITE Law is that there are regulations that guarantee the benefit of the people, namely being able to bring benefits and keep people away from evil deeds by using these cyber tools.